Percepção ambiental de educadores do campo e suas influências no processo educacional no município de Humaitá-AM - (:unkn) unknown (Universidade Federal do Amazonas, 2019)
Environmental perception is a mental activity of interaction of the individual as a medium that can be defined as an awareness of the environment by the human being. Discussions about environmental perception have been prominent in recent years, that is, the way humans interact with the world depends on their knowledge and perception of their use of natural resources. This study becomes relevant, since an investigation was carried out on the environmental perception of the educators, their relationship with nature and how they work the current problems with their students. Thus, this research had as objective to analyze the environmental perception of educators of the field and their influences in the educational process, in the Cristolândia Community in Humaitá-AM. This research is based on a qualitative approach, whose method adopted was Discursive Textual Analysis. It was developed through a field research with educators of the municipal school Antonieta Ataíde II of the public school network. In this sense, the data were collected through semi-structured interviews with the educators, in addition to the direct observation required to establish their relationship with environmental issues and educational processes. Facing the field research based on the perceptions that the teachers presented, it was possible to establish three categories on environment: Environment, Sustainable Development and Education. Through the analyzes of the data it was verified that the educators present a naturalistic vision, that is, they perceive the environment in a natural way, untouched with all its biodiversity. However, it is expected that the results achieved with this research contribute significantly to the change in conservation actions and conservation of the environment in the local community, where some environmental problems were detected such as lack of basic sanitation and lack of garbage collection. Above all, providing subsidies for this to see and feel the need to preserve the environment where one lives and especially the importance of changing habits and attitudes for a better quality of life. In addition, the results of this study can be used as a basis for the development of an education program for the development of the Cristolândia Community, in order to propose strategies for enhancing the individuals' environmental perception and the development of critical and ethical postures, thus, changing behaviors and value judgments that lead to greater environmental awareness.
Keywords: Educação ambiental; Educadores; OUTROS